The Effect Of Green Accounting On Profitability In Manufacturing Companies Sub-Sector Cement Sector In 2020-2022 - Nilam Santika; Titin Nur Azizah; Intan Pandini; Maria Yovita R. Pandin (Lembaga Pengembangan Kinerja Dosen, 2023)
Green Accounting is an accounting system that regulates between companies and the surrounding environment. Green Accounting can provide useful information for business people to manage, design, and evaluate related company systems in order to have a positive impact on the surrounding environment and the general public. This research aims to recognize the effect of Green Accounting on profitability in the manufacturing industry of the lower industrial zone and chemical cement sub-zone in 2020-2022. The research was conducted using quantitative methods. It was found that Green Accounting has a positive effect on the profitability of manufacturing companies. This is evidenced by the results of calculations with the research variables of environmental performance and the use of environmentally friendly products, which refer to the sustainability reports of manufacturing companies in the cement sub-sector in 2020-2022.